Efficacy and challenges of anti-PD1 in MSI-H mCRC: a case report on concurrent infections and ir-AIHA - Pei, Xiaxia; Zhao, Jun; Luo, Ruiying; Da, Lijun; Li, Enxi; Zhu, Hao; Li, Yanhong; Luo, Yaoting; Tian, Kun; Wang, Zhiping; Song, Feixue (Frontiers in Oncology, 2024)
Anti-programmed cell death protein 1 (PD-1) therapy has demonstrated notable efficacy in treating patients with deficient mismatch repair/high microsatellite instability (dMMR/MSI-H) metastatic colorectal cancer (mCRC). However, its clinical application is fraught with challenges and can lead to significant immune-related adverse events (ir-AEs). In this report, we present a complicated case of an mCRC patient with MSI-H and mutations in β2M and LRP1B proteins, complicated by concurrent bacteremia and liver fluke infection, who received first-line anti-PD1 therapy. The patient exhibited a positive response to anti-PD1 treatment, even in the presence of concomitant antibiotic and anti-parasitic interventions.Additionally, the patient experienced immunotherapy-related autoimmune hemolytic anemia (ir-AIHA), a rare hematological ir-AE, which was effectively treated later on.Immunotherapy represents a pivotal and highly effective approach to tumor treatment. Baseline assessment of the MMR and MSI status is a crucial step before initiating immunotherapy, and regular ongoing assessments during the treatment course can facilitate early recognition of any secondary complications, enabling prompt intervention and ensuring optimal therapeutic outcomes. Overall, a multidisciplinary diagnostic and therapeutic algorithm can help maximize the therapeutic benefits of immunotherapy.